2020
DOI: 10.1002/dc.24439
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 expression in cell‐blocks of non‐small cell lung cancer: The impact of prolonged fixation

Abstract: Introduction In the selection of non‐small cell lung cancer (NSCLC) patients for immunotherapy, specimen processed as cell blocks (CBs) may be the only available material to assess PD‐L1 expression. Therefore, optimal CB preparation becomes paramount. In this context, here we assessed whether inadequate fixation time might be one of the pre‐analytical factors affecting PD‐L1 expression. Methods Ex vivo CBs from placental (n = 3) and NSCLC (n = 8) resection specimens were obtained. PD‐L1 staining was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In this study, we retrospectively analyzed a total of 167 advanced stage NSCLC PD-L1 positive patients (≥1%) who were referred to our referral clinic for the molecular evaluation of at least five driver genes, namely, EGFR , KRAS , BRAF , ALK and ROS1 . In our experience, both histological ( n = 110, 65.9%) and cytological ( n = 57, 34.1%) samples were analyzed, strongly supporting the evidence that evaluation of PD-L1 expression levels and molecular profiling of advanced stage NSCLC patients is feasible by using both types of specimens [ 21 , 22 , 29 , 30 ]. In this context, studies have shown that NGS (both DNA- and RNA-based approaches) represents a valid solution to analyze clinically relevant biomarkers simultaneously in small tissue samples [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In this study, we retrospectively analyzed a total of 167 advanced stage NSCLC PD-L1 positive patients (≥1%) who were referred to our referral clinic for the molecular evaluation of at least five driver genes, namely, EGFR , KRAS , BRAF , ALK and ROS1 . In our experience, both histological ( n = 110, 65.9%) and cytological ( n = 57, 34.1%) samples were analyzed, strongly supporting the evidence that evaluation of PD-L1 expression levels and molecular profiling of advanced stage NSCLC patients is feasible by using both types of specimens [ 21 , 22 , 29 , 30 ]. In this context, studies have shown that NGS (both DNA- and RNA-based approaches) represents a valid solution to analyze clinically relevant biomarkers simultaneously in small tissue samples [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 61%
“…PD-L1 IHC/ICC evaluation was performed with a validated laboratory developed test (LDT), consisting of the use of Dako’s concentrate 22C3 anti-PD-L1 primary antibody with a Ventana’s detection systems on the BenchMark XT platform, or by using the companion diagnostic kit SP263 assay (Ventana Medical Systems, Tucson, AZ, USA) [ 29 , 30 ]. The level of PD-L1 expression was determined by using tumor proportion score (TPS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CBs were prepared using the Shandon Cytoblock Cell Block Preparation System (Thermo Scientific, Waltham, MA) according to the manufacturer's instructions, as previously described [15]. The original hematoxylin and eosin (H&E)-stained slides were examined by two different pathologists to outline the area of interest with respect to representative cellularity.…”
Section: Samplesmentioning
confidence: 99%
“…Indeed, CB preparatory techniques may vary significantly depending on several factors, that is, the choice of the fluid medium used for the FNA needle rinse (formalin, saline or alcohol‐based fixatives followed by formalin post‐fixation), the fixation time, and the method of concentration. 19 , 21 , 22 , 23 , 24 Despite the lack of standardized preparation protocols, several lines of evidence have demonstrated that the type of fixative does not affect PD‐L1 staining. In fact, Wang et al 21 observed that fixation with formalin only, methanol/alcohol only, or both did not affect PD‐L1 expression.…”
Section: Pre‐analytic Issues: Does the Sample Type Matter?mentioning
confidence: 99%